2001
DOI: 10.1001/archinte.161.3.454
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on Pain, Function, and Quality of Life After Total Hip and Knee Arthroplasty

Abstract: With increasing life expectancy and elective surgery improving quality of life, age alone is not a factor that affects the outcome of joint arthroplasty and should not be a limiting factor when considering who should receive this surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
232
5
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 367 publications
(283 citation statements)
references
References 26 publications
(33 reference statements)
30
232
5
10
Order By: Relevance
“…We compared postoperative pain, KSS, KSFS, and satisfaction and complication rates between patients 80 years or older and a younger cohort who underwent TKAs. Currently, these outcomes are uncertain in the literature owing to small sample sizes [4,20], limited followup [12,16,20], and the absence of comparator groups [2,11,13]. We therefore determined whether increasing age adversely affects postoperative (1) pain level, (2) KSS and KSFS, and (3) complication rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared postoperative pain, KSS, KSFS, and satisfaction and complication rates between patients 80 years or older and a younger cohort who underwent TKAs. Currently, these outcomes are uncertain in the literature owing to small sample sizes [4,20], limited followup [12,16,20], and the absence of comparator groups [2,11,13]. We therefore determined whether increasing age adversely affects postoperative (1) pain level, (2) KSS and KSFS, and (3) complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…An appreciation of key outcomes such as postoperative pain and function beyond this initial period is crucial, however, and in particular how they compare with outcomes of a younger patient cohort so that we can understand any differences between these groups. In addition, reporting of complication rates is highly variable [12,16,26]. In part, this can be attributed to varying methods of complication recording among authors [21], small samples sizes [4,20], limited followup [12,16,20], and the absence of a comparator group [2,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…The current literature provides contradictory conclusions as to whether gender influences the outcomes of TKA [3,7,9,11,14]. We therefore asked whether gender, age, and preoperative pain are associated with the prevalence of moderate-severe pain after knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In three small prospective studies of under 300 patients each, neither age nor gender was associated with any difference in prevalence of substantial pain up to 6 months [9] or up to 12 months [3] or with higher WOMAC pain at 6 months post-TKA [7]. On the contrary, a multinational randomized study of 860 TKA patients reported worse pain in women on the WOMAC pain scale at 1 and 2 years post-TKA, but no age differences [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation